Osteoarthritis - Ratih Fitriati (Jurnal KESANS : Kesehatan dan Sains, 2022)
Osteoarthritis (OA) is the most common joint disorder in the community and is chronic in nature and is the most common joint disease in adults to the elderly worldwide. The disease most commonly affects the joints in the knees, hands, feet, and spine and is relatively common in the shoulder and hip joints. The diagnosis of OA was made on the basis of appropriate radiological and clinical findings. The most common predilection for OA is the lower extremities, namely the knees and hips so that OA is the most common cause of lower extremity disability in the elderly. Method: The method used in writing this literature review is a literature review. The writing of this article is based on data from several sources originating from related, latest journals and from trusted journal publication websites such as NCBI, Pubmed, Elsevier, Google Scholar, Clinical Orthopedics and Related Research, and other related portals. Conclusion: Osteoarthritis is a joint disorder that is often found in adults and the elderly. OA is known to most commonly affect the knee joint. There are several risk factors for OA, namely age, gender, obesity, genetics, excessive physical activity, history of trauma and joint surgery, and other disease conditions that usually attack the joints. Diagnosis is made clinically, radiologically, and with laboratory assistance. Management includes pharmacological and non-pharmacological therapy